Pemikiran Sarvepalli Radhakrishnan dan Relevansinya terhadap Isu Toleransi Beragama di Indonesia - Renan Joyo, Puspo; Murtiningsih, RR. Siti; Tjahyadi, Sindung (Jayapangus Press, 2023)
Indonesia is a plural country in many aspects, including: religion, customs, culture, language, and others. In fact, plurality has not only positive, but also negative impacts. Therefore, tolerance is an important value to maintain harmony in Indonesia. The purpose of this research is to examine Sarvepalli Radhakrishnan's thoughts and their relevance to the issue of religious tolerance in Indonesia. This study is intended to present alternative ideas on religious tolerance from Hinduism, especially the advaitic framework through Radhakrishnan's thought. Methodologically, this research is literature research on the thoughts of figures. Qualitative paradigm is used in this research with the material object is religious tolerance according to Sarvepalli Radhakrishnan. Research data is obtained through document studies. Data analysis includes interpretative, holistic and descriptive. The results of this study show that religious tolerance according to Radhakrishnan is assimilation, non-discrimination and respect for the values of religions, and the ultimate goal is brotherhood. The basis of Radhakrishnan's thoughts on religious tolerance: 1) God as the ineffable ultimate reality. Thus, the truth is possible to be present in every religion, and 2) Tat Twam Asi is a non-dual form of religious awareness and experience (advaita), which implies unity, compassion, overcoming differences and conflicts.